Transition and turbulence control - Gad-el-Hak, Mohamed; Tsai, Her Mann (Lecture notes series (National University of Singapore. Institute for Mathematical Sciences), 2005)
This volume contains articles based on lectures given at the Workshop on Transition and Turbulence Control, hosted by the Institute for Mathematical Sciences, National University of Singapore, 8–10 December 2004. The lecturers included 13 of the world's foremost experts in the control of transitioning and turbulent flows. The chapters cover a wide range of subjects in the broad area of flow control, and will be useful to researchers working in this area in academia, government laboratories and industry. The coverage includes control theory, passive, active and reactive methods for controlling transitional and turbulent wall-bounded flows, noise suppression and mixing enhancement of supersonic turbulent jets, compliant coatings, modern flow diagnostic systems, and swept wing instabilities.